Endoscopic Characteristics of Dysphagia in Multiple System Atrophy Compared to Parkinson's Disease. Issue 3 (13th November 2021) - Vogel, Annemarie; Claus, Inga; Ahring, Sigrid; Gruber, Doreen; Haghikia, Aiden; Frank, Ulrike; Dziewas, Rainer; Ebersbach, Georg; Gandor, Florin; Warnecke, Tobias
ABSTRACT: Background: Dysphagia is a major clinical concern in multiple system atrophy (MSA). A detailed evaluation of its major endoscopic features compared with Parkinson's disease (PD) is lacking. Objective: This study systematically assessed dysphagia in MSA compared with PD and correlated subjective dysphagia to objective endoscopic findings. Methods: Fifty‐seven patients with MSA (median, 64 [interquartile range (IQR): 59–71] years; 35 women) underwent flexible endoscopic evaluation of swallowing using a specific MSA–flexible endoscopic evaluation of swallowing task protocol. Findings were compared with an age‐matched cohort of 57 patients with PD (median, 67 [interquartile range: 60–73] years; 28 women). In a subcohort, subjective dysphagia was assessed using the Swallowing Disturbance Questionnaire and correlated to endoscopy findings. Results: Patients with MSA predominantly showed symptoms suggestive of oral‐phase disturbance (premature spillage, 75.4%, piecemeal deglutition, 75.4%). Pharyngeal‐phase symptoms occurred less often (pharyngeal residues, 50.9%; penetration/aspiration, 28.1%). In contrast, pharyngeal symptoms were the most common finding in PD (pharyngeal residues, 47.4%). Oral symptoms occurred less frequently in PD (premature spillage, 15.8%, P < 0.001; piecemeal deglutition, 1.8%, P < 0.01). Patients with MSA had a greater risk for oral‐phase disturbances with increased disease severity ( P < 0.05; odds ratio, 3.15). Patients with MSA showed a significantly higher intraindividual interswallow variability compared with PD. When correlating Swallowing Disturbance Questionnaire scores with endoscopy results, its cutoff, validated for PD, was not sensitive enough to identify patients with MSA with dysphagia. We developed a subscore for identifying dysphagia in MSA and calculated a new cutoff (sensitivity 85%, specificity 100%). Conclusions: In contrast with patients with PD, patients with dysphagic MSA more frequently present with oral‐phase symptoms and a significantly higher intraindividual interswallow variability. A novel Swallowing Disturbance Questionnaire MSA subscore may be a valuable tool to identify patients with MSA with early oropharyngeal dysphagia. © 2021 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society